Soil monitoring and land cover/land use assessment on the Blue Nile River Watershed, Blue Nile State – Sudan/ using remote sensing and other techniques - El-Hag Hamed, Abass Mohamed; Ishag, El-Mamoun Haroun Osman; Gumaa, Yousif Suleiman Abdalla; Wedatallah, Motasim Hyder Abdelwahab (Journal of agricultural, environmental and veterinary sciences, 2023)
The study was carried out along the course of the Blue Nile from the Ethiopian-Sudanese border in the south to the borders of the Blue Nile state with Sennar state in the north. The study area was determined by establishing a buffer around the course of the Blue Nile, with a width of 20 km (10 km at each side of the river), Blue Nile state. The study attempted to update some information in the study area regarding land use/ land cover, soil properties and contour map. To facilitate forest inventory and field work. The study area was divided into equal area to four zones (A, B, C and D), 783 sites and soil sample samples were taken and classified using the land cover classification system (LCCS). The fieldwork and survey began with four practical groups, a group for each zone within the period 1 December 2015 to 5 March, 2016 in a total area of approximately 346483.42 ha. Remote sensing and fieldwork data analysis showed that there are significant changes in land use/ land cover and soil properties are in the study area (1990 to 2015). Zones A and B (South of Rosieris Dam) are mainly composed of clay soil, while the soil of Zones C and D (North of Rosieris dam) is mainly loamy soil. the study indicate that 13%, 11%, 22% and 19% from zone A, B, C and D respectively lies within the slightly acidity (pH 5.5 to 6.5), while 87%, 87%, 78% and 81% of the same zone respectably was natural soil and 2% of zone B classified as Slightly alkaline soil (pH 8) and more than 50% of the total area classified as neutral to slightly acidity, which is suitable for most crops and natural vegetation covers.SP% analysis showed that more than 80% of soils samples in the study area have SP% values greater than 40% which characterized combination of silt, loam and clay. The study indicate that the change in the patterns of land cover/ land use systems is found to be mainly due to civil war and economic crises with no clear signs of climatic change.
Keywords: Blue Nile River; Land use/ land cover change; Soil monitoring; remote sensing and LCCS